Improving Sensitivity in Ultrasound Molecular Imaging by Tailoring Contrast Agent Size Distribution: In Vivo Studies - Jason E. Streeter; Ryan Gessner; Iman Miles; Paul A. Dayton (Molecular Imaging)
Molecular imaging with ultrasound relies on microbubble contrast agents (MCAs) selectively adhering to a ligand-specific target. Prior studies have shown that only small quantities of microbubbles are retained at their target sites, therefore, enhancing contrast sensitivity to low concentrations of microbubbles is essential to improve molecular imaging techniques. In order to assess the effect of MCA diameter on imaging sensitivity, perfusion and molecular imaging studies were performed with microbubbles of varying size distributions. To assess signal improvement and MCA circulation time as a function of size and concentration, blood perfusion was imaged in rat kidneys using nontargeted size-sorted MCAs with a Siemens Sequoia ultrasound system (Siemans, Mountain View, CA) in cadence pulse sequencing (CPS) mode. Molecular imaging sensitivity improvements were studied with size-sorted α v ß 3 -targeted bubbles in both fibrosarcoma and R3230 rat tumor models. In perfusion imaging studies, video intensity and contrast persistence was ≈8 times and ≈3 times greater respectively, for “sorted 3-micron” MCAs (diameter, 3.3 ± 1.95 μm) when compared to “unsorted” MCAs (diameter, 0.9 ± 0.45 μm) at low concentrations. In targeted experiments, application of sorted 3-micron MCAs resulted in a ≈20 times video intensity increase over unsorted populations. Tailoring size-distributions results in substantial imaging sensitivity improvement over unsorted populations, which is essential in maximizing sensitivity to small numbers of MCAs for molecular imaging.